Molecularly imprinted electrochemical sensor prepared on a screen printed carbon electrode for naloxone detection - Lopes, Frederico (2017)
Naloxone (NLX) is a pharmaceutical used as opioid antagonist. A molecular imprinted polymer electrochemical sensor for simple and rapid detection of NLX was prepared through the modification of commercial available screen printed carbon electrode (SPCE). The SPCE was modified with multi-walled carbon nanotubes (MWCNT) by drop coating to increase the signal response and improve the sensitivity. The MIP preparation was carried out via in situ electropolymerization using 4-aminobenzoic acid (4-ABA) as functional monomer. The morphology of the obtained sensor was characterized by scanning electron microscopy (SEM). Several parameters controlling the preparation and performance of the MIP sensor were studied and optimized. The electrochemical behavior of NLX at MIP and control non-imprinted (NIP) sensor was evaluated by differential pulse voltammetry (DPV), demonstrating a better MIP response and the success of the imprinting. The proposed MIP/MWCNT/SPCE sensor showed a linear relationship between peak current intensity and NLX concentration in the range between 0.25 and 10.0 μM, with limits of detection (LOD) and quantification (LOQ) of 0.20 μM and 0.67 μM respectively. The repeatability and reproducibility were also tested with relative standard deviations (RSD) of 4.6 and 9.6% respectively. Moreover, the applicability of the method was successfully confirmed with detection of NLX in biological samples (urine and human serum). The sensor is promising to be used for screening NLX in point-of-care people with opioid overdose.